A new species of Eutypella (Xylariales, Ascomycota) based on multi-locus phylogeny and morphology from Motuo, China - Zhu, Anhong; Yang, Zhanen; Guan, Haowen; Qu, Zhi; Ma, Hai-Xia (Phytotaxa, 2025)
A preliminary account of Diatrypaceae species from the hitherto widely unexplored mountain forests in Motuo of Southwest China was carried out. An undescribed Eutypella species, namely Eutypella gelinensis, was described and illustrated as a new species based on morphological and molecular (ITS and TUB) data. Eutypella gelinensis is characterized by circular or elongate ostioles with a conspicuous red-brown petaloid layer and moderately to extremely curved, subhyaline to buff ascospores. Morphological differences and phylogenetic analysis of the new species are elaborated.